Controlled synthesis of hyperbranched polythioether polyols and their use for the fabrication of porous anatase nanospheres. Issue 22 (24th July 2015) - Huang, Xinhua; Hoang, Trinh Thi Kim; Lee, Hye Ri; Park, Huiju; Cho, Jin Ku; Kim, Yongjin; Kim, Il
<x xml:space="preserve">Abstract</x> A series of new hyperbranched polymers bearing multiple ether, thioether, and hydroxyl groups are synthesized by the oxyanionic ring‐opening multi‐branching polymerization of the AB3 type monomer prepared by the click reaction of 4‐vinyl‐cyclohexene‐1, 2‐epoxide with 1‐thiolglycerol. The resulting HBPs are proven to be good "molds" to control the nucleation and growth of titanium‐oxo‐species during a sol–gel mineralization process, yielding discrete porous anatase nanospheres (30–100 nm).